2021
DOI: 10.3390/w13020115
|View full text |Cite
|
Sign up to set email alerts
|

Succession of Microbial Community in a Small Water Body within the Alluvial Aquifer of a Large River

Abstract: Nitrogen is one of the essential elements limiting growth in aquatic environments. Being primarily of anthropogenic origin, it exerts negative impacts on freshwater ecosystems. The present study was carried out at the nitrate-vulnerable zone within the alluvial aquifer of the large lowland Drava River. The main aim was to investigate the ecosystem’s functionality by characterizing the bacterial and phytoplankton diversity of a small inactive gravel pit by using interdisciplinary approaches. The phytoplankton c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 123 publications
(109 reference statements)
0
0
1
Order By: Relevance
“…The proportional abundance of Actinobacteriota (1.3%) in this study was obviously lower than that in other studies, in which it was reported up to 5%-20% (He et al, 2017;Yu et al, 2018). The abundance of Actinobacteriota has been proved to be strongly correlated with nitrogen cycling, and it can thrive under oligotrophic conditions and be suppressed with high organic matter and inorganic nutrient availability (Kulašet al, 2021;Wang et al, 2021). The impact of shellfish farming on nitrogen cycling has been investigated in previous reports by analyses of water/sediment quality parameters (Erler et al, 2017;Jiang et al, 2020;Pan et al, 2021).…”
Section: Discussioncontrasting
confidence: 81%
“…The proportional abundance of Actinobacteriota (1.3%) in this study was obviously lower than that in other studies, in which it was reported up to 5%-20% (He et al, 2017;Yu et al, 2018). The abundance of Actinobacteriota has been proved to be strongly correlated with nitrogen cycling, and it can thrive under oligotrophic conditions and be suppressed with high organic matter and inorganic nutrient availability (Kulašet al, 2021;Wang et al, 2021). The impact of shellfish farming on nitrogen cycling has been investigated in previous reports by analyses of water/sediment quality parameters (Erler et al, 2017;Jiang et al, 2020;Pan et al, 2021).…”
Section: Discussioncontrasting
confidence: 81%